2015
DOI: 10.1021/acs.molpharmaceut.5b00295
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of Coamorphous Drug–Amino Acid Mixtures

Abstract: Two coamorphous drug-amino acid systems, indomethacin-tryptophan (Ind-Trp) and furosemide-tryptophan (Fur-Trp), were analyzed toward their ease of amorphization and mechanism of coamorphization during ball milling. The two mixtures were compared to the corresponding amorphization of the pure drug without amino acid. Powder blends at a 1:1 molar ratio were milled for varying times, and their physicochemical properties were investigated using XRPD, (13)C solid state NMR (ssNMR), and DSC. Comilling the drug with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…spectrum of the precipitate, except that the peaks in the ARG-IND CA spectrum were broader, which is typical of an amorphous material [33,34]. The narrower peaks in the current spectrum were indicative of the more crystalline nature of the precipitate.…”
Section: Investigation Of the Arg-ind Precipitatementioning
confidence: 91%
“…spectrum of the precipitate, except that the peaks in the ARG-IND CA spectrum were broader, which is typical of an amorphous material [33,34]. The narrower peaks in the current spectrum were indicative of the more crystalline nature of the precipitate.…”
Section: Investigation Of the Arg-ind Precipitatementioning
confidence: 91%
“…FTIR spectra revealed that Nap and Ind formed heterodimers interacting via intermolecular hydrogen bonds in the co-amorphous mixture, which explains the high stability for the sample with equal molar ratio drug (11,12). Although it has not been possible to detect specific interactions within co-amorphous Ind-Trp by FTIR (14) and co-amorphous IndTrp and Fur-Trp by ssNMR (16), the deviation from the Gordon-Taylor equation indicates that the largest increase in physical stability can be expected at around 50 mol% drug. The modified…”
Section: Co-amorphous Drug-amino Acid Combinations Without Strong Intmentioning
confidence: 98%
“…Co-amorphous Ind-Trp and Fur-Trp mixtures containing 50 mol% drug have previously been prepared by ball milling for 90 minutes and investigated by FTIR and ssNMR in order to characterize molecular interactions within each of the co-amorphous systems (14,16). In neither of the two systems, it was possible to identify specific interaction sites (besides possible π-π interactions) although the actual T g s for the co-amorphous systems are higher than the T g s calculated by the Gordon-Taylor equation, suggesting interactions between the drug and the amino acid.…”
Section: Co-amorphous Drug-amino Acid Combinations Without Strong Intmentioning
confidence: 99%
See 2 more Smart Citations